Air quality model for Austria: development and evaluation of ozone forecasts. (1st January 2011) - Hirtl, Marcus; Krüger, Bernd C.; Baumann-Stanzer, Kathrin; Skomorowski, Paul
An overview of the main findings of recent sensitivity studies and evaluations of ozone forecasts of the Air Quality model for Austria (AQA) is presented. Before the operational forecasts were started at the ZAMG, studies with different model input were conducted to find the appropriate model set-up. The performance of the chemical mechanisms CB-IV and SAPRC99 is shown for a hot period with numerous exceedances of ozone thresholds in August 2003. The operational model forecasts of ozone concentrations in 2006 and 2007 are evaluated with the observations of 121 air quality stations in Austria. In addition to the evaluation of the operational forecasts, sensitivity studies with different input parameters for the model were conducted. The results of the implementation of the emission model SMOKE for biogenic emissions are shown for a selected period in 2007 and reveal the importance of these emissions in comparison with the anthropogenic contribution.